Extremely hard, α-Mn type high entropy alloy coatings. (15th March 2020) - Sha, Chuhan; Zhou, Zhifeng; Xie, Zonghan; Munroe, Paul
Abstract: FeMnCoCrC high entropy alloy coatings were deposited onto high speed steel substrates using magnetron sputtering under a range of substrate bias voltages. These coatings exhibited a novel α-Mn crystal structure and highly refined columnar grains. Higher bias voltages promoted strong texture development through favouring (332)-oriented grains along the coating growth direction, as well as the formation of well-defined twin boundaries. The -80 V coating possessed a high hardness (~12.5 GPa), more than triple that of its fcc-structured bulk counterpart. This is attributed to the cumulative effects of the α-Mn structure, strong texture, grain refinement and the presence of twin boundaries. Graphical abstract: Image, graphical abstract